Norethisterone Related Drug Induced Liver Injury: A Series of 3 Cases - Choudhary, Narendra S. (J Clin Exp Hepatol, 2017)
Drug induced liver injury (DILI) is uncommon and severe forms are associated with significant morbidity and mortality. Female sex hormones (estrogens and progestogens) related DILI generally occur with estrogen component. Progesterone component related DILI are infrequently reported. Norethisterone is commonly used drug in gynecologic practice to prevent excess per vaginal bleeding. We report 3 cases of Norethisterone related DILI manifesting as significant rise of transaminases. All of these patients took Norethisterone for prolonged periods and improved completely after withdrawal of drug.